2019
DOI: 10.1029/2018wr022730
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling of Mixing‐Limited Bimolecular Chemical Reactions in Poiseuille Flow

Abstract: We consider the fast irreversible bimolecular chemical reaction A+B→C in the Poiseuille flow through a channel, in which A displaces B. This system allows to systematically study the impact of the interaction of interface deformation and diffusion on mixing and reactive transport. At early times, the reaction is diffusion controlled. With increasing time, advection begins to dominate and we find enhanced reaction efficiency due to the deformation of the interface between the two reactants. For times larger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 58 publications
5
35
0
Order By: Relevance
“…This occurs for times larger than D , at which the growth of the mixing region can be characterized by dispersive growth in terms of the constant hydrodynamic dispersion coefficient D * . This has also been observed in other reactive transport experiments and simulations (de Anna, de Anna, Jiménez-Martínez, et al, 2014;Jose & Cirpka, 2004;Perez et al, 2019).…”
Section: Dynamics Of Reactive Mixingsupporting
confidence: 84%
“…This occurs for times larger than D , at which the growth of the mixing region can be characterized by dispersive growth in terms of the constant hydrodynamic dispersion coefficient D * . This has also been observed in other reactive transport experiments and simulations (de Anna, de Anna, Jiménez-Martínez, et al, 2014;Jose & Cirpka, 2004;Perez et al, 2019).…”
Section: Dynamics Of Reactive Mixingsupporting
confidence: 84%
“…Hence, at late times the actual mixing state M AB converges toward the ideal well‐mixed case MABtruenormalc¯ and scales with t 1/2 . Looking closely at the log‐log scale plot (Figure 3b), and taking the modeled mixing state M AB as a proxy for the amount of reaction, we see that it does reproduce trends observed in mixing‐limited systems such as simple Poiseuille flows (e.g., Perez et al., 2019, Figure 7).…”
Section: Concentration Fluctuation Dynamicssupporting
confidence: 52%
“…Porta et al (2012), Porta et al (2016), Chiogna and Bellin (2013), Alhashmi et al (2015), Perez et al (2019), and Benson et al (2019) have demonstrated capturing reactant and product concentrations at early time. Perez et al (2019) uses the enhanced stretched lamella approach called dispersive lamella which is able to capture effects of the diffusion on the evolving interface. Benson et al (2019) use reactive-particle-tracking (RPT) to upscale reactive transport in a Hagen-Poiseuille flow with a preasymptotic dispersion coefficient similar to that derived by Wang et al (2012).…”
Section: Introductionmentioning
confidence: 99%